Controlled Ultrasonic Motor for Servo-Drive Applications - Maas, Jürgen; Schulte, Thomas; Grotstollen, H.
This paper deals with an advanced speed control scheme for inverter-fed travelling waveultrasonic motors. It is implemented as an additional outer control loop of an underlaid voltage andtravelling bending wave vector controller and verified by measurements on a prototype drive. Thenovel speed control is using an inverse contact model by a neural network, trained by measured valuesof speed and torque, in order to compensate the nonlinear torque generation of the motor. Since thereference values of the bending wave control are calculated from the desired torque value by the neu-ral network, first an open loop control of the drive ́s torque is feasible and second common speed con-trol schemes, well performing in common electrical drives, can be applied. Thus, the so equippedultrasonic motor-drive meets requirements for applications in the field of servo-drives e.g. robotics.